The Nutrition Quality of Cassava Leaf Silage with Different Fermentation Lengths - Hindratiningrum, Novita; Fitria, Restuti; Santosa, Setya Agus (ANIMAL PRODUCTION, 2023)
This study aimed to observe the nutrition contents (crude protein/CP, crude fiber/CF, crude fat/CFat, and nitrogen-free extract/NFE) of cassava leaf silage using rice bran and starter EM-4 as the source of carbohydrates, with different fermentation lengths. The Completely Randomized Design was applied to four treatments (fermentation lengths) and five replicates. The treatments were P0 = 0-day fermentation, P1 = 7-day fermentation, P2 = 14-day fermentation, and P3 = 21-day fermentation. The obtained data were subjected to Analysis of Variance (ANOVA) and continued with Duncan’s Multiple Range Test (DMRT). The results showed that the fermentation lengths significantly affected the nutrient content of cassava leaf silage. The post hoc DMRT indicated different levels of CP, CFat, and CF across treatments, while R0 and R1 shared equal NFE. The difference and similarity of nutrient quality across treatments were due to different phases in fermentation. Day 0 through day 7 was the lag phase, and day 14 was the exponential phase which would decline until day 21 when it reached the stationary phase. Conclusively, 14-day fermentation was the best duration to make cassava leaf silage.